Multiplying Light Harvest Driven by Hybrid‐Reflections 3D Electrodes Achieves High‐Availability Photo‐Charging Zinc‐Ion Batteries. Issue 15 (1st March 2023) - Zhang, Minggang; Pan, Longkai; Jin, Zhipeng; Wang, Xiao; Mei, Hui; Cheng, Laifei; Zhang, Litong
Abstract: Independent photo‐charging technologies based on aqueous zinc‐ion batteries (ZIBs) are promising candidates for next‐generation renewable energy systems. The conflict between light utilization and electrochemical performance in the planar electrode severely limits the availability of photo‐charging ZIBs. Herein, 3D light‐trapping structures (LTSs) are proposed and applied in a rigid VO2 /C@SiCuOC electrode. A hybrid‐reflection effect driven by LTSs is employed to improve light‐harvesting efficiency. The suitable energy levels of VO2 and C ensure charge transport, while the rigid SiCuOC support meets the stability requirements. Such a 3D VO2 /C@SiCuOC electrode exhibits a multiplying photo‐response current density of 42.2 µA cm −2 (≈400% of the plate) and delivers a higher energy density (0.19 mWh cm −2 at 0.51 mW cm −2 ). More importantly, in a realistic environment (dark for 16 h and light for 8 h), the photo‐charging ZIBs integrated into a roof exhibit an exciting open circuit voltage of 3.176 V (three in series) and supply electricity continuously. The high strength (over 9 MPa) of the photo‐charging ZIBs inherited from the 3D rigid electrode further enables its practical application. The enhanced performance of the photo‐charging ZIBs obtained from structural optimization provides unique inspiration for next‐generation clean energy harvest/storage systems. Abstract : A hybrid‐reflection 3D electrode with light‐trapping structures, which exhibits a multiplying light harvest compared to the plate, is developed utilizing a 3D‐printed SiCuOC as supporting, and VO2 /C as surface active materials. The photo‐charging zinc ion batteries constructed using the hybrid‐reflection 3D electrode provide synergistic performance enhancement, indicating strong potential in clean energy harvest and storage.